2023
DOI: 10.3389/falgy.2022.1058865
|View full text |Cite
|
Sign up to set email alerts
|

Profile of aeroallergen sensitizations in allergic patients living in southern Vietnam

Abstract: BackgroundClimatic and geographical characteristics may alter the plant distribution and thereby the patterns of allergens.ObjectiveTo evaluate the profile of allergen sensitization in patients in southern Vietnam and its association with allergic diseases.MethodsWe collected data of 423 patients who visited the Unit of Allergy and Clinical Immunology, University Medical Center, Vietnam from 2014 to 2021, from their medical records. Patients underwent skin prick tests to the 12 most common aeroallergens. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Shek et al hypothesized that cross-reaction with dust mite allergy contributes to mild cases of shellfish allergy. 20 Interestingly, sensitization to house dust mites is common in Vietnam, about 6.3-30.9% in the population and even higher in patients with allergic diseases (49.6-59.8%) 37,38 Therefore, it can lead to primary sensitization with dust mite tropomyosin, a panallergen and a major allergen in shellfish and mollusk. Other pan-allergens were highlighted, such as arginine kinase, troponin C, and triosephosphate isomerase, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Shek et al hypothesized that cross-reaction with dust mite allergy contributes to mild cases of shellfish allergy. 20 Interestingly, sensitization to house dust mites is common in Vietnam, about 6.3-30.9% in the population and even higher in patients with allergic diseases (49.6-59.8%) 37,38 Therefore, it can lead to primary sensitization with dust mite tropomyosin, a panallergen and a major allergen in shellfish and mollusk. Other pan-allergens were highlighted, such as arginine kinase, troponin C, and triosephosphate isomerase, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we did not evaluate the sensitization to inhaled allergens. Nonetheless, the study conducted by Trinh et al [26] showed a high prevalence of sensitization to Dermatophagoides pteronyssinus (59.2%), Dermatophagoides farinae (42.9%), and Blomica tropicalis (42.9%) in patients with AD living in southern Vietnam. The allergen sensitization in children tends to shift from FAs to inhaled allergens when they grow up.…”
Section: Discussionmentioning
confidence: 99%